Estimate of Glomerular Filtration Rate among Players of A West African Football Team During A Competition... - VIGAN, JACQUES; AGBODJOGBE, Wilfrid Kpèdétin; BIGOT, CÉDRIC EGNONWA PARFAIT; AHOUI, SERAPHIN; Bigot, André (My University, 2017)
Introduction: A football match cauld cause transient Introduction ddverse dfects in the players' kidney function. The purpose of thi' ~tudy is to determine the development of glomerular Physical ilctivity is associilted with disruptions of the body's filtration rate rnong football players during a match and a horneostaqis These disruptions can cause the developrnent [lf compelition in Benin. ildaptive responsc:s which, in the long term, are translatcd IIIt ) the physicill condition. However, the maintenance (and mu~;t Methods: It was a cross-sectional and descriptive study often the improvement) of the individual's heJlth condiliun conducted from No'vember 2015 to May 2016. Participants requires that constraints due ta the physical activity <lre included black footballer, aged above 1-7' years, who has perfectly tolerated by the body fIl been residing in Benin for at least one year, attending regul<lr training sessions and having given his informed The benefits of regular physical activity are reflected thmugf, 'onsent to participate, in the study. During a serics of 4 an improvement of the well-being, a reduction in the incidenu: ln tches, slood sampling was regularly cëirried out before, justat the énd and 24 hours after each match, Glomerular' of cJrdio-Vilscular diseJses and il longer lifespiln [2J. filtration rate (GFR) was estimated by CKD-EPI formula from I<idneys élilow mëlintainirlg their own normill value of the bloCid creatinine. individual's vital signs. They are involved in the elimination L)f many substilnces, the control of acids-bases balance and bloot! Results: A total of 14 play€rs wère included in eadi match. The participating players livere averagely aged 23 ± 2.21 pressure regulation [3,41. yearo and had 2years of experience in firstdivision football. I<idneys play multiple and complex roles, however thè' The estlmate of the players' medium GFR during the lst Glomerulilr FiltrJtion Rate (GFR) is the best evidence of ail th(~sc match was 129.35 ± 17.39 ml/min/1.73m2 before the beginning, 90,31± 17.39 ml/min/l,73rn2 at the end and functions ;51 GFR is the qUilntirative variable which best dnlifll', 23.96 ± 18.72 rnl/min/1.73m2 2/1 houl-q later. During a 4kidney function, and it is a vital parameter in the assesSl!1cIll of match competition, the GFR declines at the end of each renal function [6J. In cllnical practice, the glomerular filtratiUl In;;ltch and rise up again in the next 24 hour . rate is cstimated from blood biomarkers of which the most uscd is the determinJtion of serum creJtinine [n ConClusion: The glomer,ular filtration rate declines drastically and transiently during a match of football Physical activity leads to significant changes in the ren,JI competition in a hot and humid dimate. There is need for hemodynamics and in the urinary excretion of electrolytes iilld players to rehydrate before, during and after each match. proteins [8,9] During physical effort, the increase in blood flow to Lhl' lTluscles leads ta il decline of the splanchnic drld rcnal pel fu,iol1 This decline is dlrcctly prof.JUr!;orlal to the degree iJrld dUI Jrion
Keywords: Benin; CKD-EPI; Glomerular filtration rate; Football; Hot and humid climate